2022
DOI: 10.1039/d2tb00690a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks as a therapeutic strategy for lung diseases

Abstract: This review focuses on the design and application of MOF-based drugs against lung diseases, and discusses the possibility of preparing MOF-based inhalable formulations and the challenges and opportunities of MOFs in clinical applications targeting lung diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 198 publications
0
3
0
Order By: Relevance
“…Despite recent advances in the treatment of multiple lung infections in the clinic, the opportunity to create targeted nanosystems that are easier to use in the clinic has not been realised. 343 Any advancement in pulmonary nanomedicine delivery systems should aim to make treatment as effective as possible while minimizing unintended side effects. Xia et al 344 found that targeting of platelet-derived extracellular vesicles (PEVs) can deliver [5-(p-fluorophenyl)-2-uryl] thiophen-3-formamide (TPCA-1) into the lung to quell the local CS in acute lung injury (Figure 20).…”
Section: Lung Targeted Nanomedicine Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in the treatment of multiple lung infections in the clinic, the opportunity to create targeted nanosystems that are easier to use in the clinic has not been realised. 343 Any advancement in pulmonary nanomedicine delivery systems should aim to make treatment as effective as possible while minimizing unintended side effects. Xia et al 344 found that targeting of platelet-derived extracellular vesicles (PEVs) can deliver [5-(p-fluorophenyl)-2-uryl] thiophen-3-formamide (TPCA-1) into the lung to quell the local CS in acute lung injury (Figure 20).…”
Section: Lung Targeted Nanomedicine Deliverymentioning
confidence: 99%
“…Despite recent advances in the treatment of multiple lung infections in the clinic, the opportunity to create targeted nanosystems that are easier to use in the clinic has not been realised 343 . Any advancement in pulmonary nanomedicine delivery systems should aim to make treatment as effective as possible while minimizing unintended side effects.…”
Section: Multiple Therapies Including Nanotherapy For Management Of Csmentioning
confidence: 99%
“…Metal ions are of concern due to their significant impact on the health and disease of living organisms. [1,2] Among them, iron is the most abundant essential transition metal ion in the human body and plays a vital role in biological and environmental systems. [3][4][5] Excess or deficiency of ferric ions can lead to various diseases such as heart failure, liver damage, kidney damage, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions are of concern due to their significant impact on the health and disease of living organisms [1,2] . Among them, iron is the most abundant essential transition metal ion in the human body and plays a vital role in biological and environmental systems [3–5] .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOF) are formed via coordinate bonding between organic linkers and metal ions. MOFs synthesized using a variety of materials and exhibiting versatile functionalities have been applied in environmental science, sensor separation, catalysis, and drug delivery. However, MOFs used for drug delivery and their building blocks should be biodegradable . For example, sugars such as starch and lactose are safe and biodegradable.…”
Section: Introductionmentioning
confidence: 99%